THE APPLICATIONS OF THEORY PLANNED BEHAVIOR ON KNOWLEDGE SHARING AT FAMILY BUSINESS - Puterisari, Dwi Utami; Wening, Nur (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
This research is conducted to know the behavior of sharing knowledge that be planned from the first generation of family business to the next generation, in order to make a sustainable and imperishable of family business. The research is used the planned behavior theory by Ajzen in order to developing and testing the model research of variables which influencing the intention of many knowledges and behaviors of the owner of family business. The result of the research shows that the owner of the business proved make a planning about behavior in many knowledges empirically and the major determinant of  the behavior in many knowledges is intention owned. For more complete, the result shows that the control of behavior be prepared positively will be influence the intention and the behavior of many knowledges. The subjective norm did not influence the intention and the behavior in wide range of knowledge in positive way, while, the positive intention gives the effect to  the behavior in variety of knowledges. The other result shows that the positive attitude influeces to the intention and the behavior in variety knowledges.